Effects Of Acalypha Hispida: Restorative Perspectives of Stz-Induced Diabetic Peripheral Neuropathy in Sprague-Dawley Rats - V. Shrirao, A.; Y. Bhiwgade, N.; S. Mohale, D.; I. Kochar, N.; V. Chandewar, A. (Journal of Neonatal Surgery, 2025)
Oxidative stress has a key role in the pathogenesis and progress of diabetic peripheral neuropathy (DPN), one of the most common and debilitating complications of diabetes mellitus. Acalypha hispida is a treasure of multiple pharmacological properties and presently leaves of this plant have been explored to evaluate the protective effects against Streptozotocin-induced diabetic neuropathy in rats. Male Sprague-Dawley rats were injected with Streptozotocin (STZ) (60 mg/kg i.p.) to induce diabetes. Post 21 days of STZ induction, animals were treated with ethanolic extract of Acalypha hispida (200 mg/kg, and 400 mg/kg of EEAH) for forty two consecutive days. Followed this, all animals were evaluated for the levels of blood glucose, cholesterol (CH), lipid peroxidation (LPO), Catalase (CAT), Superoxide Dismutase (SOD). Neuropathic pain markers like hyperalgesia, allodynia and motor deficits were assessed before and after the treatment with STZ and EEAH. STZ treated rats exhibited elevated levels of blood glucose, CH, LPO, CAT, SOD in comparison to control rats. EEAH treatment significantly decreased blood glucose levels, CH, LPO, CAT, SOD levels, and restored pro-oxidants status. Further, decrease in hyperalgesia and restorative changes following EEAH treatment suggested the neuroprotective potential of Acalypha hispida leaves in diabetic rats. Current study reveals that EEAH exert protective and curative effects against STZ-induced diabetic neuropathy in rats which might be due to its antioxidant, anti-inflammatory, and antiapoptotic properties.